Study of Greenhouse Gas Emission on the Semarang-Demak 1A Toll Road Project - Arditya Panca Saputra; Andri Prasetyo Nugroho; Febriyanti Angelia Ginting; Habib Abdillah Nurusman (International Journal of Science and Environment (IJSE), 2026)
This study estimates carbon dioxide (CO₂) greenhouse gas (GHG) emissions during the construction phase of the Semarang–Demak Toll Road Project 1A. Motivated by the significant contribution of the infrastructure sector to global GHG emissions, hence the problem formulation is focused on identifying the main emission sources. The aim of the study is to reveal the dominant emission sources and to formulate decarbonization recommendations to reduce environmental impacts and support national emission reduction targets. The study employs a quantitative approach based on the Technical Guidelines for Estimating CO₂ GHG Emissions in Road Construction (No. 07/P/BM/2014) issued by the Directorate General of Highways, Ministry of Public Works and Public Housing, which adapts the IPCC methodology using emission calculation formulas and specific emission factors. Activity data from January 2023 to October 2025 were analyzed according to emission Scopes and work divisions based on General Specifications Revision 3. A qualitative approach complements the analysis by evaluating the effectiveness of decarbonization strategies through observation and document review. The results show total emissions of 6,942,173 tons CO2-eq, with Scope 3 dominating 5,688,286 tons CO2-eq (81.957%) from Division 10 Concrete Structures due to intensive cement production, Scope 1 at 741,235 tons CO2-eq (10.677%), and Scope 2 at 512,652 tons CO2-eq (7.385%). Decarbonization strategies include Green Construction, innovation in work methods and technology, BIM integration in Lean Construction, monitoring based on PP No. 22/2021, AMDAL, and RKL-RPL, and the use of renewable energy such as solar power plants (PLTS) and solar panels for Scope 2 electricity supply.